Cardiac manifestations in Fabry disease - Linhart, A; Lubanda, J C; Palecek, T; Bultas, J; Karetová, D; Ledvinová, J; Elleder, M; Aschermann, M (Journal of inherited metabolic disease, 2001)
Fabry disease is an X-linked recessive genetic disorder of glycosphingolipid metabolism, due to deficiency of the lysosomal enzyme alpha-galactosidase A. The disease is characterized by the progressive intracellular lysosomal accumulation of neutral glycosphingolipids throughout the body, including the cardiovascular system. It has been reported that cardiac involvement could be the sole manifestation of the disease in some patients. Myocardial abnormalities are characterized mainly by left ventricular (LV) wall thickening without significant cavity dilatation, the most frequent abnormal structural pattern being concentric LV hypertrophy (LVH). In some patients the disease mimics a typical hypertrophic obstructive cardiomyopathy. According to our experience, systolic function is largely preserved in a large majority of affected individuals. In contrast, mild to moderate impairment of diastolic filling is a relatively common finding, representing probably the most important cause of dyspnoea in patients with Fabry disease. However, in a relatively large population of affected patients, severe diastolic dysfunction, typical of restrictive cardiomyopathy, was not found. Valvular structural abnormalities are frequent due to valvular infiltration. In several patients, hypertrophy of papillary muscles and/or systolic anterior motion of the mitral leaflets associated with LV outflow obstruction may aggravate the mitral valve dysfunction. We did not confirm the previously reported high prevalence of mitral valve prolapse. Valvular regurgitation seems to be relatively frequent but mostly non-significant. Electrocardiographic changes in Fabry disease are multiple and include atrioventricular (AV) conduction abnormalities (abbreviation of the P-R interval or AV blocks), signs of LVH and repolarization abnormalities. Our observations suggest that conduction defects and repolarization changes are present predominantly in subjects with LV structural abnormalities. Cardiac symptoms in patients with Fabry disease include shortness of breath on effort (related to LV diastolic dysfunction), vasospastic and/or exertional angina pectoris (due to LVH, endothelial dysfunction and/or fixed coronary artery stenosis) and syncope (related to AV blocks or LV outflow obstruction). The extent of cardiac involvement, in particular LV mass assessment, could represent an ideal surrogate endpoint for evaluating the efficacy of specific therapies.
Keywords: srdce; nemoci srdce; Fabryho nemoc; Fabry Disease; srdeční chlopně; srdeční komory; Heart Diseases; Electrocardiography; Heart Ventricles; Ventricular Function, Left; funkce levé komory srdeční; Heart Valves; lidé; Heart; Humans; elektrokardiografie